γ-Glutamylcysteine Ameliorates Oxidative Injury in Neurons and Astrocytes In Vitro and Increases Brain Glutathione In Vivo - Le, Truc M. (2010)
γ-Glutamylcysteine (γ-GC) is an intermediate molecule of the glutathione (GSH) synthesis pathway. In the present study, we tested the hypothesis that γ-GC pretreatment in cultured astrocytes and neurons protects against hydrogen peroxide (H(2)O(2))-induced oxidative injury. We demonstrate that pretreatment with γ-GC increases the ratio of reduced:oxidized GSH levels in both neurons and astrocytes and increases total GSH levels in neurons. In addition, γ-GC pretreatment decreases isoprostane formation both in neurons and astrocytes, as well as nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear translocation in astrocytes in response to H(2)O(2)-induced oxidative stress. Furthermore, GSH and isoprostane levels significantly correlate with increased neuron and astrocyte viability in cells pretreated with γ-GC. Finally, we demonstrate that administration of a single intravenous injection of γ-GC to mice significantly increases GSH levels in the brain, heart, lungs, liver, and in muscle tissues in vivo. These results support a potential therapeutic role for γ-GC in the reduction of oxidant stress-induced damage in tissues including the brain.